Cyber security in international relations: Risks and prospects - Zinchenko, Oleksandra (Eximia, 2025)
The purpose of this article is to determine the essence, theoretical foundations, and legislative aspects of regulating cyber security in international areas, as well as researching risks and prospects for improving cyber security at the international level. The problems of ensuring cyber security at the international level, as well as the key cyber threats that have the greatest damage in the cyber security of the countries of the world, have been studied. The main directions of international cooperation on ensuring cyber security at the international level have been determined. The peculiarities of cyber security of the EU countries are characterized, as well as the legislative acts that regulate this activity and are distributed to all members of the union. The main characteristics of cyber security of the NATO countries and the BRICS association, as well as the peculiarities of cyber security regulation, taking into account the difference in the legal framework of the participating countries, are provided. The characteristics of the cyber security of China, Japan and Great Britain are highlighted, as well as the basics of cyber security of Ukraine are defined: problems and prospects for its further development, probable directions of borrowing world experience in cyber protection of national interests.